دراسة علاقة المزارعين بالوحدات الإرشادية في محافظتي اللاذقية وطرطوس وسبل تفعيلها - صقر, إبراهيم; العبد الله, محمد; إبراهيم, سلام (Latakia University Journal -Biological Sciences Series, 2016)
هدفت الدراسة إلى التعرف على علاقة المزارعين بالوحدات الإرشادية الزراعية في محافظتي اللاذقية وطرطوس، حيث شملت العينة 342 مزارعاً متواجداً ضمن نطاق عمل 48 وحدة إرشادية زراعية، عاملة في محافظتي اللاذقية وطرطوس. وأظهرت النتائج أن نحو 75% من العينة هم مزارعون، و25% مزارعات، 90% منهم متزوجون، ونحو 40% منهم يحملون الشهادة الثانوية وما فوق، و نحو 25% منهم مهنتهم الأساسية الزراعة، 40% منهم لا يزورون الوحدات الإرشادية، وأهم أسباب عدم الزيارة كانت انشغال المزارعين بعمل آخر غير الزراعة أثناء الدوام الرسمي للوحدات الإرشادية، و ذلك بالنسبة لـ42% من المزارعين. وبينت النتائج أيضاً أن الطابع الخدمي يغلب على عمل الوحدات الإرشادية الزراعية، وذلك تبعاً لرأي المزارعين، وكانت درجة تأدية الوحدات الإرشادية الزراعية لخدماتها منخفضة بحسب رأي 75% من المزارعين، كما بينت الدراسة وجود علاقة ارتباط بين كل من الجنس، والعمر، و الوضع التعليميللمزارع، ودرجة تنفيذ الوحدات للأنشطة الإرشادية، و درجة تنفيذ الوحدات الإرشادية الزراعية للخدمات، ومصادر معلومات المزارعين، علماً أن كل هذه العوامل كان لها علاقة ارتباط معنوية مع مدى تواصل المزارعين مع الوحدات الإرشادية الزراعية.The study aimed to identify the relationships between Farmers and agricultural extension units in Lattakia and Tartus governorates, the sample included 342 Farmers live in the work scope of 48 agricultural extension units, located in Lattakia and Tartus Governorates, the results showed that 75% of the sample were male and 25% were femal,90% were married, 60% had high school education, agriculture work was the main job for 25% of farmers, 40% of them did not visit extension units and the mean reason for that was farmer had another job during the work time of extension units, for 42% of farmers .Also the result showed that extension units perform agriculture services more than extension service with low level of performance ,according opinion of 75% of farmers. The study showed significant relationship between sex (male, female), age, farmer's education , degree of performance of extension service, degree of performance of agriculture service in the extension units and information sources of farmers ,all these factors had significant relationship with the degree of Farmer's communication with agricultural extension units.